Harmony Retreat : Menyatu Dalam Perbedaan Sebagai Strategi Pengembangan Wisata Religi Berbasis Toleransi Di Pura Langgar Bali - Suarmana, I Wayan Restu (Jurnal Kajian Pariwisata Dan Perhotelan, 2025)
Pura Langgar in Bangli, Bali, is a rare symbol of tolerance and cultural acculturation between Hindus and Muslims. Despite its potential, this site has not been optimally developed as a religious tourism destination that highlights diversity values. This study aims to examine strategies for developing religious tourism at Pura Langgar, based on interfaith tolerance, using a literature study and descriptive qualitative analysis. The findings indicate that the development of spiritual retreat packages, cross-cultural education, and tolerance-based learning, supported by local community homestays and collaboration with religious leaders as well as the Tourism Office, has the potential to strengthen the destination’s appeal. With synergy among all stakeholders, Pura Langgar can become a model for inclusive religious tourism in Indonesia.